2018
DOI: 10.1038/s41598-018-19508-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of purely endogenous, self-regulatory control of attention

Abstract: Stimulus-driven orienting of attention toward a novel, salient stimulus is a highly adaptive behavior. In an opposing vein, it is also crucial to endogenously redirect attention to other stimuli of behavioral significance if the attended stimulus was evaluated to be unimportant. This stimulus-driven orienting and subsequent reorienting of attention are known to be mediated by similar neural substrates. However, this might be because reorienting was triggered by a sensory transition exogenously capturing attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…It is now thought that attention is not a unitary process but involves two distinct neuronal systems. The ventral network implements exogenous (stimulus-driven) attention, while the dorsal parieto-frontal network [ 121 ] and anterior insula network implement endogenous (self-directed, volitional, goal-directed) control. The systems converge in the lateral prefrontal area [ 122 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is now thought that attention is not a unitary process but involves two distinct neuronal systems. The ventral network implements exogenous (stimulus-driven) attention, while the dorsal parieto-frontal network [ 121 ] and anterior insula network implement endogenous (self-directed, volitional, goal-directed) control. The systems converge in the lateral prefrontal area [ 122 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In alerting tasks, endogenous and exogenous attention interact, and there is an increase both in global perceptual sensitivity and in the perception of exogenous spatial cues. Recently, Han and coworkers [9] showed that anterior insula (AI) is the key structure in endogenously reorienting of attention after reflexive attention is captured by a salient distractor. In tasks in which the participants know that a target will appear after a cue, brain responses will be optimized, and endogenous attention will be deployed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to exogenous spatial cues, vigilance tasks induce changes in endogenous and exogenous attention interactions and perceptual sensitivity. The sensitivity is reduced when stimulus onset is predicted, because an exogenous cue and the prediction time prepare participants to take over next stimulus [9]. Neurocognitive attentional processes related to the environmental input generate brain waves and electrical potentials with specific frequencies and amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, our study will focus on a specific network including three brain regions: anterior insula (AI), DLPFC, and ACC, known to control attention during cognitively demanding tasks (Cauda et al, 2011). Anterior insula has been demonstrated to intervene in the arousal regulation during alertness tasks (Craig, 2002;Critchley, Melmed, Featherstone, Mathias, & Dolan, 2002); it has been associated with a bottom-up capture of focal attention particularly during exogenous attention (Han et al, 2018). More specifically, AI feeds the ACC with the necessary information, which in turn spreads out these signals to the cortical regions.…”
mentioning
confidence: 99%